2020
DOI: 10.3390/su12072785
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self-Assessment Indicators for Motorcycle Riders in Thailand: Application of the Motorcycle Rider Behavior Questionnaire (MRBQ)

Abstract: The purposes of this research are (1) to create a motorcycle riding behavior measurement model for a Thai population by Motorcycle Rider Behavior Questionnaire (MRBQ) modification with exploratory factor analysis (EFA); (2) to verify the measurement model by second-order confirmatory factor analysis (second-order CFA); and (3) to define the guidelines of the self-assessment report for Thai people in terms of riding motorcycles. Collected data were distributed among four areas: metro-municipalities, municipalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
1
21
0
3
Order By: Relevance
“…The findings of this study clearly show that the underlying significant factors affecting traffic accidents were risky driving behavior, followed by unsafe environmental, and vehicle conditions. The vital factors involved in occurrence of incidents were human, vehicles, and environment, of which the contribution of human factors was 95%, road and environment 28%, and vehicles 8% (Evans, 2012;Zhang, 2019;Uttra et al, 2020). This result also agrees with prior studies (Shinar, 2007;Petridou & Moustaki, 2000;Sasfarzadeh & Pooryari, 2006;Hijar et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings of this study clearly show that the underlying significant factors affecting traffic accidents were risky driving behavior, followed by unsafe environmental, and vehicle conditions. The vital factors involved in occurrence of incidents were human, vehicles, and environment, of which the contribution of human factors was 95%, road and environment 28%, and vehicles 8% (Evans, 2012;Zhang, 2019;Uttra et al, 2020). This result also agrees with prior studies (Shinar, 2007;Petridou & Moustaki, 2000;Sasfarzadeh & Pooryari, 2006;Hijar et al, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…Numerous studies have focused on the factors influencing personal behavior for accident prevention, and have indicated that gender, age, driving experience and marital status etc. are significantly associated with safe driving (Uttra et al, 2020;Aden, 2019;Helal, et al, 2018;Zhang, et al, 2013). Risky behavior is a direct cause of road accidents, such as drunk driving, speeding, mobile phone use while driving, and motorbike rider not wearing a helmet, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The MRBQ has been widely used in studies of motorcycle riding behavior, such as Özkan, et al [27]. Uttra, et al [28] developed the MRBQ as an assessment tool for the riding behavior of Thai people, consisting of 26 questions for four factors: traffic errors, control errors, stunts, and safety equipment. We selected these four factors to further study the motivating theory of behavioral practice in structural equation modeling.…”
Section: Motorcycle Rider Behavior Questionnaire (Mrbq)mentioning
confidence: 99%
“…Riders without near-miss and crash experience reported fewer traffic violations than those who had experienced (Stephens et al, 2017). Traffic errors were the most common cause of blunders or poor decisions when riding the MTW (Uttra et al, 2020). Their offence rates, crash, and near-miss crash rates increase by more than 20% for every one-unit increase in traffic errors.…”
Section: Traffic Errormentioning
confidence: 99%